Komodifikasi Ruang Privat dalam Tayangan Pernikahan Atta Halilintar & Aurel Hermansyah - Fakhrizal Octaviana; Yadi Supriadi (Bandung Conference Series: Journalism, 2023)
Abstract. At the beginning of 2021, the Indonesian television world was enlivened by a series of broadcasts of the weddings of top Indonesian artists. Atta Halilintar and Aurel Hermansyah. The popularity of both is an important source when the media displays a broadcast because it will be the center of attention of the audience. One of the highlights is the broadcast "Ikatan Cinta Atta & Aurel Special Akad and Thanksgiving Akad" on RCTI on April 3, 2021. In this broadcast, the wedding ritual has been commodified with private space. This research seeks to reveal the commodification efforts made by RCTI. This study uses the Norman Fairclough model of critical discourse analysis. Norman Fairclough's critical discourse analysis uses three stages, namely text analysis, Discourse Practice Analysis, and Sociocultural Practice Analysis. This broadcast is suspected of commodifying public space or public interests for the sake of the political economy of the media by showing the wedding of a phenomenal figure which takes quite a long time. Abstrak. Pada awal tahun 2021, dunia pertelevisian Tanah Air diramaikan oleh serangkaian tayangan acara pernikahan artis papan atas Indonesia. Atta Halilintar dan Aurel Hermansyah. Popularitas keduanya menjadi salah satu sumber penting ketika media menampilkan sebuah tayangan karena akan menjadi pusat perhatian khalayak. Salah satu yang menarik adalah tayangan “Ikatan Cinta Atta & Aurel Spesial Akad dan Syukuran Akad” di RCTI pada 3 April 2021. Pada tayangan ini ritual pernikahan telah dikomodifikasi dengan ruang privat. Penelitian ini berusaha mengungkap upaya komodifikasi yang dilakukan oleh RCTI. Penelitian ini menggunakan metode analisis wacana kritis model Norman Fairclough. Analisis wacana kritis Norman Fairclough menggunakan tiga tahap yaitu analisis teks, Analisis Discourse Practice, Analisis Sociocultural Practice. Tayangan ini diduga mengkomodifikasi ruang publik atau kepentingan publik demi kepentingan politik ekonomi media dengan cara menayangkan pernikahan sosok fenomenal yang memakan waktu cukup lama.